Tibial hemimelia: a surgical approach for bone reconstruction and lengthening - Fraga, Carlos Eduardo Cabral; Vilela, Maria Eduarda Freitas Barbosa Arantes; Bueno, Vinicius Ferreira Pires; Leão, Gustavo Teixeira; Sola, Yesmin Naji; Resende, Marcos Henrique Alves (Journal of the Foot & Ankle, 2024)
Tibial hemimelia is a rare condition with a reported incidence of approximately one in one million live births. Although tibial hemimelia can vary its presentation, it often presents a shortened lower limb associated with deformities in the knee and ankle. The objective of this study is to present a case of tibial hemimelia and the surgical technique performed to correct the deformity and bone lengthening using a circular external fixator in several stages. A 15-year-old male patient was evaluated, presenting Jones type 3 tibial hemimelia (visible distal part, but no proximal) in the right lower limb associated with congenital clubfoot and ankle deformity. Studying and planning the patient’s case was essential to classify and define the best treatment. These treatments can be flawed and often reach amputation. In the case described, several surgical approaches were performed with the objective of reconstructions and deformity correction, followed by limb lengthening, presenting excellent results. Level of evidence IV; Therapeutic studies; Case Report.